Soil tillage and sugarcane planting: an assessment of cost and economic viability - Amorim, Fernando Rodrigues De; Patino, Marco Tulio Ospina; Santos, David Ferreira Lopes [UNESP] (São Paulo - Escola Superior de Agricultura "Luiz de Queiroz", 2021)
Yield and profitability levels in sugarcane crops demonstrate the importance of the agricultural practices adopted, especially for soil preparation and planting systems. This study evaluated the costs involved in 40 alternative methods for the establishment of sugarcane crops resulting from the combination of eight soil preparation systems and five planting options, followed by an assessment of the economic viability of sugarcane production for suppliers and sugar mills. Data were collected from 31 sugar mills and 42 suppliers in São Paulo State, Brazil, from the 2016/17 season. The cost analysis and discounted cash flow analysis were used to calculate economic viability. Localized soil preparation with a fixed application rate of inputs (soil amendments) and mechanized planting with a variable application rate of fertilizers were the least costly systems to establish the sugarcane crop. Regarding the sugarcane establishment system, the medium–sized sugar mills were the most economically viable when compared to independent sugarcane producers. There was no significant difference in cost to establish sugarcane crops across the various sized groups of suppliers and we identified that costs rose as the size of the sugar mills increased.
Keywords: Saccharum spp; mechanization; variable rate; yield; profitability